Regulatory signal transduction pathways for class IIa histone deacetylases - Parra, Maribel; Verdin, Eric (Current opinion in pharmacology, 2010)
The class IIa histone deacetylases (HDACs), HDAC4, 5, 7, and 9, have crucial roles in the development of the immune system and other organs, including brain, heart, and muscle. In addition to their catalytic domain, they are characterized by a large amino-terminal extension. The amino-terminal domain is subject to reversible phosphorylation, which controls their nucleo-cytoplasmic distribution. Unphosphorylated, class IIa HDACs remain in the nucleus, bound to chromatin, and repress transcription. Upon phosphorylation, they shuttle out of the nucleus, allowing derepression of their target genes. Thus, the nucleo-cytoplasmic translocation is associated with derepression of target genes. Recent studies identified the kinases and phosphatases that regulate the nucleo-cytoplasmic shuttling of class IIa HDACs. Here we will summarize this rapidly evolving field with a particular focus on the immune system.